Hallucinating God? The cognitive neuropsychiatry of religious belief and experience - McKay, R (KLI Publications, 2004)
The claim that religious belief is delusional is evaluated using a current cognitive neuropsychiatric model of delusion formation and maintenance. This model explains delusions in terms of the conjunction of two cognitive deficits - the first a neuropsychological deficit giving rise to an anomalous perceptual experience, the second a deficit in the machinery of belief evaluation. It is argued that to provide an account of religious beliefs as delusional within this model, two requirements must be met: 1. Plausible candidates for the first factor must be put forward; and 2. There must exist individuals with aberrant religious perceptions who do not develop deluded beliefs about those experiences. With regard to requirement 1, a range of "neurotheological" research is reviewed. The second stated requirement is addressed via consideration of "mystic atheists" - individuals who have had mystical experiences yet have not adopted religious beliefs as a result. A variety of problematic issues for the above account are tackled. It is concluded that insight into the motivational basis for religious beliefs, when combined with OCCAM's principle of scientific parsimony, allows a plausible case to be made for religious belief as delusional, provided that a particular construal of belief pathology is adopted.